CLINICAL ASPECTS OF A NEW CORONAVIRUS INFECTION (COVID-19) - Sh. E. Turaeva (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Resume. The appearance of COVID-19 has set tasks for healthcare professionals related to the rapid diagnosis and provision of medical care to patients. Currently, information about the epidemiology, clinical features, prevention and treatment of this disease is limited. It is known that the most common clinical manifestation of a new variant of coronavirus infection is bilateral pneumonia, in 3-4% of patients the development of acute respiratory distress syndrome (ARDS) was registered.